Koperasi Unit Desa dalam Pencegahan Ilegal Drilling - Rizky Adi Nugraha; Lego Karjoko; Waluyo Waluyo (Jurnal Discretie, 2021)
This study aims to understand and analyze the implementation of Illegal Drilling in Oil and Gas mining in Indonesia as well as to understand and analyze the role of Village Unit Cooperatives to prevent Illegal Drilling in Oil and Gas mining in Indonesia in order to achieve the welfare of rural communities. This law is a type of prescriptive normative legal research using a statute approach. The types of legal materials used are primary legal materials and secondary legal materials. The technique of collecting legal materials that support and relate to the presentation of this research is document study (library study). Document study is a tool for collecting legal materials through written legal materials using content analysis. The results of this study indicate that the role of KUD itself is still not able to prevent illegal drilling, there are still activities that harm the community, which is contrary to the Law of the Republic of Indonesia Number 22 of 2001 concerning Oil and Gas such as management without a permit so that it is included in illegal management. , this illegal drilling activity violates the rules of Law No. 22 of 2001 concerning Oil and Gas which has been set by the government. The state also suffers losses because petroleum is one of the assets of the state and also damages the environment in the vicinity of illegal drilling activities. It is difficult for the government to control the mining of old oil wells or illegal drilling because it has become the livelihood of the community, but it was found that the hope that the exploitation of old wells can contribute to Regional Original Income (PAD) is increasingly far from reality. Likewise, the purpose of community empowerment cannot be carried out properly.